P14 Early predictive markers of clinical response to Mepolizumab- a clinical, biochemical and immunogenic perspective. (11th November 2022) - Pang, YL; Clifford, R; Matthews, L; Clayton, C; Lee, H; Rakkar, K; Stewart, I; Harrison, T; McKeever, T; Sayers, I; Shaw, DE
Abstract : Introduction: Severe asthma is a debilitating condition affecting 4–10% 1 of all patients with asthma in the UK. Over the last few years monoclonal antibodies targeting interleukin 5 (IL-5) and eosinophilic inflammation have been more widely used, however the response to drugs such as Mepolizumab is heterogeneous and approximately 30% of patients do not respond to treatment after 12 months 2 . The delivery of anti-IL5 therapies is costly, and requires subcutaneous injection. A robust early predictor of response is needed. We describe the clinical, biochemical and immunological markers of treatment response to Mepolizumab from a single centre prospective study. Methods: This was a prospective observational cohort study at a single tertiary asthma centre in the UK. Patients meeting NICE endorsement criteria for Mepolizumab were invited to participate. 42 patients were recruited with 37 patients completing the study. Clinical demographics, serum samples and patient-reported outcome measures were obtained at baseline (pre-initiation) and 12 weeks after commencing Mepolizumab. Responder status at 12 months was determined by NICE guidelines and validated by blinded physicians. Serum cytokine levels representing Type 1, 2, and 17 inflammation were measured using Luminex. Immunogenicity testing to Mepolizumab was outsourced. Results: 24 patients were classified as responder and 13 as non-responders. Improvement in the Severe Asthma Questionnaire (SAQ) score by the minimally clinically important difference (0.50) in the first 12 weeks of treatment led to a 6-fold increase in odds of responding to Mepolizumab (OR 6.75, CI: 1.51–30.16, p=0.012). Serum cytokine levels at baseline or 12 weeks did not predict treatment response to Mepolizumab. Prognostic modelling from anti-Mepolizumab antibody levels was not feasible as only one patient had antibodies identified by the assay. Conclusion: SAQ was identified as a potential tool to guide treatment decisions. Further validation to establish its sensitivity and specificity in the UK severe asthma cohort initiating Mepolizumab is needed. References: Holgate ST, Polosa R. The mechanisms, diagnosis, and management of severe asthma in adults. Lancet . 2006;368 (9537):780–93 Harrison T, Canonica GW, Chupp G, Lee J, Schleich F, Welte T, et al . Real-world Mepolizumab in the prospective severe asthma REALITI-A study: initial analysis. Eur Respir J . 2020;56 (4).